Without Anyone Noticing - Wallo, Olga (Iluminace, 2005)
An example of the process and importance of dubbing William Shakespeare's complete dramatic works into Czech: Czech Television purchased a cycle of 34 plays, filmed by the British BBC in the 1980s. Seven of the plays were not broadcast at all, six were subtitled and the rest were dubbed.
Keywords: Czech Television; shows; dubbing